Analyzing higher education performance by entropy - TOPSIS method: A case study in Viet Nam private universities - Tien-Chin Wang; Thuy T Thu Nguyen; Binh N Phan (Measurement + Control, 2022)
The development in both quantity and quality of the system of private universities over the past time has created great opportunities for people to study and improve their qualifications and working skills. It is also challenging for educational managers to find the right university development strategy in today's competitive environment. Therefore, evaluating the effectiveness of using private universities resource to analyze training performance is considered one of the issues. In this study, the Entropy method is used to determine the weight of the criteria. Then the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is used to determine the ranking order of the private universities. Next, Spearman's rank correlation coefficient was applied to evaluate the correlation between rank-ordered variables over the 2 years of analysis selection. Finally, ANOVA was used to compare the criteria between groups of universities. The combination of methods contributes to creating an objective environment in assessing the performance of each university. Thereby, universities can see the important criteria to pay attention to, creating a premise for universities to establish strategies for development and competition. At the same time, educational leaders have the right perspective in choosing key universities to invest in finance and facilities.